Anti-angiogenic potential of ardisia crispa roots ethanolic extract and its quinone-rich fraction in mice - Awang Hamsin, Dayang Erna Zulaikha (2013)
Angiogenesis is the process of blood vessel formation which plays a crucial role in normal physiology, and also in the progression of various chronic diseases such as cancer, arthritis and such. As targeting angiogenesis has become an important strategy in the search of treatments of various debilitating ailments, it is a need-based study to identify a natural source of anti-angiogenic agent that may halt the progression of angiogenesis event. Ardisia crispa, locally known as “mata itik” (Family: Myrsinaceae) has been used in traditional Malay medicine to treat various ailments related to inflammation. Ardisia crispa roots have been shown to treat various inflammation-related diseases in several previous studies. As angiogenesis is strongly correlated with inflammation, the aim of the present study was to evaluate anti-angiogenic potential of the hexane partition of Ardisia crispa roots ethanolic extract (ACRH) and its quinone- rich fraction (QRF) on several experimental models, namely Miles vascular permeability test, murine air pouch granuloma and mouse sponge implantation test. Preliminary cyclooxygenase and soy lipoxygenase inhibitory study were also conducted to elucidate the possible pathways involved. Preliminary phytochemical screening of ACRH indicated the abundant presence of flavonoid, triterpene and tannin. Quinone- rich fraction (QRF) was separated from ACRH (38.33% w/w) and further isolated to yield a compound, namely fAC-2, indicated by a single TLC spot at Rf: 0.76. The compound was later found to be impure, when later analysed with GC-MS. Nevertheless, fAC-2 was elucidated to possess a major constituent of a benzoquinonoid compound (2-methoxy-6-undecyl-1, 4-benzoquinone), when compared with the standard data. Both ACRH and QRF were also quantified using high performance liquid chromatography (HPLC). For toxicity study, the LD50 value of ACRH was found to be 617.02 mg/kg. In Miles vascular permeability assay, the lowest dose of both ACRH and QRF (10 mg/kg) produced significant reduction in VEGF-induced hyperpermeability compared to vehicle control. In murine air pouch granuloma, ACRH and QRF displayed significant and dose-dependent angiogenic and inflammatory inhibition, in which significant reduction of vascular index and granuloma tissue weight was observed at high dose (100 mg/kg). ACRH and QRF were also shown to possess selective COX-2 inhibitory properties which were dose-dependent, though COX-1 inhibition was also observed in a lower percentage. On the other hand, ACRH and QRF did not exhibit LOX inhibitory activity. Interestingly, fAC-2 showed its selectivity towards the inhibition of COX-2, instead of COX-1, and showed to be a moderate LOX inhibitor. Thus, it can be concluded that Ardisia crispa roots showed potential anti-angiogenic properties by partly mediating COX-2 activity, as shown in the in vitro screening, and it is postulated that fAC-2 (2-methoxy-6-undercyl-1, 4-benzoquinone) displays dual COX-2 and LOX once it is purely isolated in a large scale and tested in vivo.